Constraining the spin-down timescale of the white-dwarf progenitors of Type Ia supernovae - Meng, X; Podsiadlowski, P (2013)
Justham (2011) and DiStefano et al.\ (2011) proposed that the white-dwarf progenitor of a Type Ia supernova (SN Ia) may have to spin down before it can explode. As the white dwarf spin-down timescale is not well known theoretically, we here try to constrain it empirically (within the framework of this spin-down model) for progenitor systems that contain a giant donor and for which circumbinary material has been detected after the explosion: we obtain an upper limit of a few $10^{\rm 7} {\rm yr}$. Based on the study of Di Stefano and Kilic (2012) this means that it is too early to rule out the existence of a surviving companion in SNR 0509-67.5.